(untitled) (Journal of Bangladesh Institute of Planners, 2016)
Dhaka, the capital of Bangladesh is experiencing a dramatic transformation in residential built density due to the concentration of administrative, institutional, commercial, social, recreational, small-scale industries, and their associated housing facilities. Such transformation is visible in residential built footprint, originated from low rise and low density to high density and high rise developments. This study is an attempt to explore the phenomenon of growing residential built density in a planned area, namely, Section 2 and in an unplanned area, namely, Kazipara in Mirpur Thana of Dhaka. Here the residential density has been measured according to the basic theories of density which is expressed as a number of dwelling units per acre of land in case of both gross and net density. Moreover, for better understanding and visual effect, sky view factor (SVF) is used here as a parameter of built density. For this study a detailed physical survey of the study areas was conducted. To identify the causes and consequences of the growing built density, five factors i.e. demographic, social, economic, physical (urban planning related) and environmental are considered. The study focused particularly on the residential built density, its causes and consequences in a local scale. It is revealed from the study that residential built density in city scale differs substantially from local scale. JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 27-42